The Bee Honey Market in the State of Pará, Brazilian Amazon: An Econometric Model - Silva, Joyce Monteiro da; Santos, Marcos Antônio Souza dos; Santos, Wânia Mendonça dos; Saraiva, Joyce dos Santos; Lopes, Maria Lúcia Bahia; Costa, Nilson Luiz; Soares, Bruno Cabral; Loureiro, João Paulo Borges de; Martins, Cyntia Meireles; Martins, Geany Cleide Carvalho (Journal of Agricultural Studies, 2022)
This study evaluates the effects of socioeconomic, environmental, and institutional variables on the bee honey market in the state of Pará, from 1990 to 2019. The generalized method of moments was used to create the econometric model for estimation. The results show that the supply of honey is price-inelastic and that the rate of forest deforestation strongly impacts honey production. The creation of the Federação das Associações de Apicultores do Estado do Pará was denoted an important institutional landmark for the beekeeping production chain; however, the effects of incentive policies such as rural credit are limited and do not meet the needs of beekeepers. Institutional market policies are ineffective and rarely accessed by beekeepers; however, they represent an opportunity to diversify marketing channels. Honey is a product of biodiversity that is economically classified as a superior good and its demand is price-inelastic. Honey and its derivatives lack marketing strategies to enable their competitive insertion in new markets and government programs; these would enable access to broader markets in cities and lead to the acquisition of more consumers in the future.